Pedagogical Erothetics or the Logic of Asking Questions in the Context of Digital Pedagogy - Popa, Doinița (Didactica Danubiensis, 2023)
The paper addresses a topical issue regarding the intelligent use of pedagogical erothetics as an essential component in digital pedagogy that can significantly contribute to increasing the effectiveness of online learning and teaching. By formulating and using relevant and challenging questions, educators can improve student engagement and enhance the quality of the educational experience in the digital environment. Pedagogical erothetics, or the logic of asking questions in the context of digital pedagogy, are essential aspects of practical and interactive education in the digital age. In digital environments, where information can be accessed quickly and from diverse sources, the logic of questions becomes crucial to assess students' knowledge and skills correctly.